Kamusal Açık Kent Mekânı Kullanımını Dönüştüren Bir Mekânizma Olarak Yoğunluk: Levent Bölgesi Örneği - Kıdır, Yelin (Fen Bilimleri Enstitüsü, 2015)
Kentlerin tarihinde bugünkü şekil ve içeriklerini kazandıran ana gelişmeler olarak, modernleşme, sanayileşme ve küreselleşme hareketleri sayılabilir. Bu hareketlerin ışığında, kent yoğunluğu kurgusu, kavramsal bileşenlerinin özellikleri ve diğer kent bileşenlerinin farklı etkileriyle, farklı tanımlama ve değerlendirmeler almıştır. Yoğunluk, aldığı bu değerlendirmelere bağlı olarak, seviyesi düşürülmeye veya yükseltilmeye çalışılmıştır. Örneğin tarihte, sanayileşme yüzünden iş sahası yakınlarında artmakta olan konut problemiyle yüzleşen kentlerde yoğunluğu düşürmenin yolları aranırken; küreselleşmenin hız ve tüketimine karşın sürdürülebilirliğin sağlanması amaçlanan kent merkezlerinde kaybedilen yoğunluk geri kazandırılmaya çalışılmaktadır. Bir diğer yoğunluk kurgusunun farklı yorumlanması örneği, mekânın ayrılmaz bir bileşeni olan yoğunluğun farklı sosyokültürel etmenler ile farklı ifadelere sahip olmasında yatmaktadır. Bu örneklerin gösterdiği gibi birbirinden farklı değerlendirme ve yorumlamalar sonucunda kurgulansa da, yoğunluk bir mekânda mekânın her zaman bahsedilebilen bir niteliğidir. Kent ve kentlinin içinde bulunduğu karşılıklı etkileşim ve dönüşüm süreçlerinin, mekânın ayrılmaz parçası olan mekânın yoğunluğu kurgusu üzerinden incelenmesi tezin ana problemini oluşturmaktadır. Bu inceleme, kendi iç dinamikleriyle değişmekte olan kentlerin, sosyal ilişkiler ve mekânın buluştuğu nokta olan kent ve toplumun en çok etkileşimde bulundukları yerler, yani kamusal açık kent mekânları üzerinden geçekleştirilmiştir. Tez kapsamında yoğunluk kavramının dönüştürücü etkisi ve kamusal açık kent mekânı değişimine etkisi ele alınmaktadır. Yoğunluk kurgusunun ne olduğunu ele alan kuramsal çerçeve, yoğunluğu ele alış biçimleri ve değerlendirmelerine göre kavramsal olarak incelemekte olup, kamusal açık kent mekânında nasıl gözlenmekte olduğunu tespit edebilmek adına, yoğunluğun tüm tanımları, değer ve değerlendirmelerine göre farklılıklar içeren kamusal açık kent mekânları üzerinde çalışma yapılmıştır. Levent bölgesinde yer alan, farklı niteliklere ve yoğunluk dinamiklerine sahip olan iki kamusal açık kent mekânı çalışma alanları olarak ele alınmıştır. Çalışma kapsamında anket ve sistematik gözlemlerle ele alınan kamusal açık kent mekânlarının, yoğunluğun değiştirici etkisi karşısında nasıl etkilendikleri ortaya çıkarılmaya çalışılmış, bulguların değerlendirilmesiyle yoğunluğun dönüştürücü etkisine dair, kavramsal çerçeve ve uygulama alanlarındaki sonuçlar arasındaki ilişkilerin ortaya konması hedeflenmiştir. Tez çalışması, yoğunluğu problem alanı olarak belirleyen ve bu problem doğrultusunda çalışmanın amacını, kapsamını ve sorularını açıklayan giriş bölümü ile başlamaktadır. Giriş bölümünde ortaya koyulan soruların tespit ve analizlerine yönelik olarak takip edilecek araştırmanın yöntemi ve çalışmanın organize edilmesi de ortaya konmaktadır. İkinci bölümde yoğunluk ve kamusal açık kent mekanı tanımlamaları yapılmakta ve aralarındaki ilişkinin altını çizen konular üzerinde durulmaktadır.  Araştırmanın problemlerinin incelenmesine yönelik üçüncü bölümde, Levent Bölgesi’nde yer alan, seçilen kamusal açık kent mekânlarının özellikleri ve seçilme nedenleri üzerinde durulmuş, araştırmanın yöntemi doğrultusunda yapılan çalışmalar sonucunda elde edilen bulgular belirtilmiştir. Bulguların değerlendirilmelerinin ortaya konduğu kısmı dördüncü yani sonuçların yer aldığı bölüm takip etmektedir. Dördüncü bölüm ise tez çalışması sonuçlarının değerlendirildiği, çalışmanın problemlerini ne kadar açıklayabildiğinin ve sonraki çalışmaların hangi noktalara odaklanması gerektiğinin belirtildiği sonuç bölümlerinden oluşmaktadır.

The main elements giving shape and content to the cities are the movements of modernization, industrialization and globalization.  Under the light of these movements the construction of density of cities, together with the impacts of its conceptual components and other components of the cities, have had different definitions and assessments.  Depending on these different assessments it has been tried to increase or decrease the density of cities. For example in the history, whereas the density has been tried to be lowered in cities where there is increasing problem of housing near the business areas because of industrialization; it has been tried to be increased in city centers which lost population due to the speed of globalization and consumption. Another example of different interpretation of density lies in the ground that the density, as an inseparable part of space, has different socio-cultural elements and expressions. As these examples show though there are different assessments and interpretations, density is always an important element of the space. The main problem of this thesis is the analysis of the mutual interaction and transformation processes of cities based on the density of space. This analysis has been done in public spaces which are the places where most of the interactions between people happen.  Mainly, the thesis elaborates on the transformative impact of density on public open city spaces.The theoretical framework of density setup has been analysed conceptually according to the analysis methods and assessments of density. In order to observe density in open public spaces this study has been done.  The study has been done in two open public spaces in Levent area which have different qualities and density dynamics. With questionnaires and systematic observations it has been tried to analyse how the open public spaces have been affected due to the transformative impacts of the density.The evaluation of findings contributes to the explanation of the relationship of the conceptual framework and practice. The thesis begins with the introduction chapter in which density has been defined as a problem and this section explains the aim, context and the research questions of this thesis.Moreover, according to the problem and questions of the thesis the relevant methodology will be presented. In the second chapter, the definitions of density and open public spaces and the relationship between these are presented. The third chapter aims at the analysis of the problems and elaborates on the qualities and selection reasons of open public spaces in Levent area.  The fourth chapter evaluates the findings of the study and introduces the results which identify the main points of focus in the study.  Today’s cities face three main problems. These are human-based problems due to the rapid population growth, resources consumption problems and environmental problems. It has been known that half of the population in the developing world will be living in urban areas by 2030 and even now when this process is happening people living in bad conditions in urban areas constitute the majority of the population. On the other hand, there is growing concern about the depletion of the vital resources of life and because of that people have become more sensitive about usage of resources and sustainable development. Taking into account these, there are discussions about the density problem in cities which areshaped based on these dynamics and accordingly the construction and housing conditions are being reviewed. There is a lot of research done about negative and positive impacts of density increase in urban areas and compact cities and shrinking cities are among these studies. These studies have identified various benefits of increasing the density in those areas. Preserving the nature, not losing the fertile agricultural land, decreasing the need of energy and accessibility due to the low density and forming a sustainable future are among these benefits. On the other hand, some problems like the high initial cost of infrastructure and services due to the density increase have also been identified. When the present literature is analysed, it can be seen that the leading research topic is housing since it has a lower function value in terms of users but a higher value in terms of area it covers. However, the data on the relationship between density and open public spaces is not sufficient.  The studies about the cities lack analysis on the impacts of usage of the interaction between the public spaces and density which is one of the permanent components of the urban areas. Based on this ground, this thesis aims at finding out how the changes in density in cities affect the usage of open public spaces and how this transformation as a component of city occurs. The main goal of this studyabout density and usage of open public spaces, is to contribute to the development of cities taking into account the pressure coming from the increasing density. The main research question of the study is whether there is an impact of density as a present phenomenon in the open city areas, on the diversity of usage of these areas and if so how these impacts occur.  In order to understand the concept of density and assess the dynamics it brought to the cities, the usage of open public spaces and how it interacts with other components of cities will be analysed. By this way, this study will contribute to the issue of how to include the concept and impacts of density which a sine qua non element of perpetually evolving areas of cities into the process of design and also it will contribute to the design of public open spaces which will better serve to people so that they can have higher quality lives. Levent is one of most affected areas of İstanbul from various important historical processes. The impacts of modernization which started with the public housing project of Housing and Credit Bank; the emergence of squatter houses as a result of industrialization and migration to the city in Çeliktepe region; and the development of Büyükdere Street with globalization are the important developments which shaped the region. All these mentioned dynamics affect the usage of open public spaces of the region. It should be taken into account all the components affecting the usage of public spaces have an organic integrity and have important interactions between each other. Based on this assumption, this study tries to find out the impacts of the density differences in open public spaces. Spaces are designed and used based on views advocating the increase or decrease of density as wasalsoobserved in history. The transforming effect on space of the density practices shaped by these different views is strongly related to the current world views. In Levent, the density shaped by globalization. Studies show that people define crowded places as places where there is a high density of buildings rather than a highdensity of people.
Density As A Transformative Tool For The Use Of Open Urban Public Space: The Case Of Levent District
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: yoğunluk; kamusal açık kent mekanı; density; open urban public space